The Right Method for Developing Elementary School Student’s Creative Thinking Skills - Ardilansari; Muhammad Nizaar; Haifaturrahmah; Najamudin; Emese K Nagy (Universitas Pendidikan Ganesha, 2023)
Thinking creatively is very important for students in the 21st century because the demands of the times expect creative students to discover new things with advances in science and technology. The learning method applied at this time has yet to be able to train students to think creatively. This study aims to analyze differences in students' creative thinking skills between the mind mapping method and the picture and picture method. The research method used was quasi-experimental with a posttest-only control group design. The sample used was 45 fifth-grade elementary school students. The data collection technique uses a creative thinking ability test, which consists of four indicators: the ability to think fluently, flexibly, originality, and elaboration. Data analysis used a t-test through Jeffreys's Amazing Statistics software program. The results of the data analysis showed that Cohen's d score was 0.830. These results indicate a significant difference between the two learning methods. Based on the average score and the percentage of scores obtained by students on each indicator of creative thinking, it shows that mind mapping is superior to the picture-and-picture method in developing creative thinking. It was concluded that elementary school teachers can apply the mind mapping method to develop students' creative thinking skills.